The Effect of Purchasing Welfare on Consumer Purchasing Behavior: the Role of Mediator Attitudes - Aida Azadi; Ali Zarei; Farshad Tojari (The Society of Aging and Physical Activity (SAPA), 2019)
Background. Despite the research being accomplished so far, there is no clear answer to the question whether purchasing welfare is affected by the attitude of customer purchasing behavior. Objectives. The aim of this study was to investigate the effect of purchasing welfare on consumer purchasing behavior and to assess the mediator role of attitudes in this regard. Methods. This was a descriptive-correlational study conducted using a survey method. The statistical population of the study consisted of all young consumers of sporting goods (15-30 years old) in Isfahan city. In this study, there were 23 free parameters in the proposed model. The sample size was considered for each free parameter of 15 people. Finally, 350 people were estimated. Purchasing welfare (Edley et al., 2013), attitudes (Lee and Trill, 2012) and consumer purchasing behavior (Edwards, 1998) were used as the instruments and their face and content validity and reliability were confirmed (0.75, 0.80, 0.81). Data were analyzed using Amos-22 software. Results. The research model had a favorable fit. Also, the mediator attitude was a partial relationship between purchasing welfare and purchase behavior (P < 0.05). Conclusion. Consumer welfare increased the behavior of consumer purchasing, but with the increasing consumer attitude in the relationship, the impact of purchasing prosperity on behavior increased.